2014
DOI: 10.1371/journal.pone.0111651
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Value of Excision Repair Cross-Complementation Group 1 (ERCC1) in Patients with Small Cell Lung Cancer (SCLC) Receiving Platinum-Based Chemotherapy: Evidence from Meta-Analysis

Abstract: Recently, the correlation between the efficacy of platinum-based chemotherapy and ERCC1 expression in patients with SCLC has attracted wide-spread attention, and a lot of investigations have been conducted, whereas conflicting results were presented. Therefore, we performed the present meta-analysis of eligible studies to derive a more precise evaluation of the association between ERCC1 expression and the clinical outcome in SCLC patients receiving platinum-based chemotherapy. A literature search for relevant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 46 publications
1
2
0
Order By: Relevance
“…[ 28 ] The present meta-analysis, chiefly focused on patients underwent chemotherapy, revealed that patients with increased expression of ERCC1 predisposed to be resistant to chemotherapy and a short PFS, and OS was very likely the consequence. It was consistent with the theoretical inference and the analogous meta-analyses assessing the prognostic value of ERCC1 in gastric cancer,[ 29 ] small cell lung cancer,[ 30 ] and nonsmall cell lung cancer. [ 31 ] Thus, we inferred that ERCC1 might be employed as an indicator of therapy effects and the survival outcome.…”
Section: Discussionsupporting
confidence: 86%
“…[ 28 ] The present meta-analysis, chiefly focused on patients underwent chemotherapy, revealed that patients with increased expression of ERCC1 predisposed to be resistant to chemotherapy and a short PFS, and OS was very likely the consequence. It was consistent with the theoretical inference and the analogous meta-analyses assessing the prognostic value of ERCC1 in gastric cancer,[ 29 ] small cell lung cancer,[ 30 ] and nonsmall cell lung cancer. [ 31 ] Thus, we inferred that ERCC1 might be employed as an indicator of therapy effects and the survival outcome.…”
Section: Discussionsupporting
confidence: 86%
“…In combination with PKO, other useful PDO strategies may also be used, such as adaptation to protein, epigenetic, or genetic markers recognized for their treatment-specific prognostic value (27)(28)(29)(30), or biological early efficacy markers (31,32). One such example of PDO, the use of targeted therapy tailored to genetic aberrations, has been tested in a negative trial (33), which could have had different results under the PKPDO paradigm, because most of its drugs have clinically relevant exposure-response relationships (34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44).…”
Section: Pharmacodynamic Optimization In Oncology Trialsmentioning
confidence: 99%
“…65 Preclinical studies in several cancer cell lines, including ovarian, cervical, and lung, support the hypothesis that overexpression of ERCC1 correlates with resistance to platinum-based therapies. [66][67][68][69] In a large-scale study into lung cancer treatment, it was shown that patients with ERCC1-negative tumors benefited significantly more from cisplatin treatment, whereas patients with ERCC1-positive tumors did not respond to treatment and had a poorer prognosis. 70 Furthermore, an investigation in colorectal cancer demonstrated that patients with low expression of ERCC1 had a significantly greater median survival in comparison to those expressing high levels of ERCC1, although there was no correlation with response to 5-fluoracil/oxaliplatin treatment.…”
Section: Ercc1-xpf and Xpgmentioning
confidence: 99%